Pengaruh Promosi dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan E-Wallet (Dana) di Kota Cimahi, Jawa Barat - Doni Dirgantara Asikin; Eva NurShyfa (Penerbit Goodwood, 2023)
Purpose: This study was motivated by an increase in Internet users in Indonesia, which is also followed by an increase in e-wallet users in Indonesia, although the increase is not as large as that of Internet users. This study examines the effects of promotion and customer satisfaction on e-wallet customer loyalty (DANA) in Cimahi City, West Java. Methodology: The research method used in this study is a descriptive and associative method. In this study, the unit of analysis was the individual, namely, the people of Cimahi City, West Java. Fifty respondents were included in this study were 50 respondents. Sampling by non-probability sampling and incidental sampling was the sampling technique used in this study. The method of analysis uses multiple linear analyses, in addition to testing the validity and reliability of the research instrument. Results: The results indicate that exogenous variables (promotion and satisfaction) have a partial or simultaneous influence on endogenous variables (customer loyalty). Limitations: This research was planned to involve users of the Cimahi City Fund application Dana, West Java, aged 20-34 years. Contribution: The implication of this research is that Dana can make promotions through social media by increasing discounts, collaborating with large merchants and holding giveaways so that customers are always satisfied with their promotions, giving rise to expectations and good performance when using Dana's e-wallet and Dana's e-wallet users. will be more loyal, because they always feel satisfied and do not switch to another e-wallet.